THE ANTI-OXIDANT ACTIVITIES OF ETHANOL EXTRACT OF MAHOGANY (Sweitenia mahagoni Jacq.) SEEDS IN THE LIVER TISSUES OF DIABETIC EXPERIMENTAL RATS - Eka Prasetiawan; i Ketut Mudite Adnyane; Tutik Wresdiyati (Universitas Syiah Kuala, 2017)
The aim of this research was to analyze the anti-oxidant activities of ethanol extract of mahogany seeds on the liver tissues of diabetic experimental rats to overcome oxidative stress condition. This study used male Rattus norvegicus strain Sprague Dawley which were divided into 5 groups: (i) negative control group (K-), (ii) positive control group/diabetes mellitus (DM) (K+), (iii) DM group treated with 500 mg/kg BW ethanol extract of mahogany seeds (EM), (iv) DM group treated with acarbose (KO), and (v) non-DM group treated with 500 mg/kg BW ethanol extract of mahogany seed (KE). Alloxan with dose of 110 mg/kg BW was used to induce diabetes in rats. The treatments were conducted for 28 days. At the end of treatment, the liver tissues were collected and analyzed for malondialdehyde (MDA) content using thiobarbituric acid reactive substance (TBARS) method and anti-oxidant cooper zinc superoxide dismutase (Cu,Zn-SOD) content using immunohistochemical technique. The result showed that level of MDA were significantly different (P0.05) in K-; K+; EM; KO; and KE with values were 0.81±0.17; 1.19±0.26; 1.10±0.04; 0.95±0.13; and 0.92±0.0 µmol/gram, respectively. The anti-oxidant content (Cu, Zn-SOD) of rat liver tissue in K+ lower than in K-, while anti-oxidant content in EM and KE were higher compared to K+. The study concluded that ethanol mahogany seeds extract decreased blood glucose levels and increased the anti-oxidant status in the liver tissues of diabetic rats.